THE EFFECT OF LEARNING PHYSICS WITH PROBLEM BASED INSTRUCTION (PBI) MODELS IN PHYSICS AT THE CLASSROOM - Nurdin Bukit; Satria Mihardi (Universitas Negeri Medan, 2012)
Abstract. Physics learning at school aim to know difference about using PBI model on learning outcomes on dynamic electrical in SMA Istiqlal Delitua A.Y. 2009/2010. This research is a quasy experiment and sampling was done with simple random sampling. From the data analysis and hypothesis testing is concluded, learning outcomes with conventional model to dynamic electrical is 69.13 (enough criteria). Learning outcomes with a PBI model to dynamic electrical is 80.65 (good criteria). It was based on calculation results by t test tcount = 6.82 and ttabel = 1.99, with tcount > ttabel (6.82 > 1.99), then Ha accepted and H0 rejected thus stated that there are significant differences using PBI models on result student learning on a dynamic electrical in grade 10th SMA Istiqlal Delitua A.Y. 2009/2010.